Application of the Cox Proportional Hazard Model with the Breslow Method in Inpatients with Type 2 Diabetes Mellitus at XYZ Hospital - Nuraisyah, Puteri; Zakiyah, Zahra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Type 2 Diabetes Mellitus (DMT2) is a chronic disease that is often accompanied by complications such as hypertension, anemia, and infection, which can affect the length of hospitalization and the time of clinical occurrence. The purpose of this study is to analyze the clinical factors that affect the time of occurrence in DMT2 inpatients at XYZ Hospital using the Cox Proportional Hazard regression model using the Breslow method. Secondary data from 33 patients were analyzed by including variables of age, sex, comorbidities, blood pressure, blood sugar levels, diabetes mellitus diet program, diabetic feet, and pain. Results showed that age (p = 0.076), comorbidities (p = 0.058), and pain complaints (p = 0.101) had a significant effect on the time of occurrence, while other variables were insignificant. Thus, the Cox model of the Breslow method has been shown to be effective in identifying risk factors in the clinical data of survival of DMT2 patients